Pharmacokinetic Modification of Colon Targeted Delivery systems of Tegaserod Maleate based on Osmotic Technology - R. Margret Chandira (Journal of Global Pharma Technology, 2019)
Colon targeted delivery systems of Tegaserod maleate based on osmotic technology were developed. The developed systems consisted of osmotic core (drug, osmotic agent and wicking agent), coated with semipermeable membrane (spm) containing guar gum as pore former, coated core were then further coated with enteric coating to protect the system from acidic environment of stomach. the effect of various formulation variables namely the level of wicking agent (sodium lauryl sulphate), osmotic agent in the osmotic core, the level of pore former (guar gum) in spm, were studied on physical parameters and drug release characteristics of developed formulations. Tegaserod maleate release of drug is directly related to the level of pore former, wicking agent and osmotic agent. The drug release from the developed formulations was independent of pH.  The thickness of enteric coating could prevent formation of delivery pores before contact with simulated colonic fluid, but had no effect on drug release. Result of spm studies showed the formation of in-situ delivery pores in the membrane from where the drug release occurred, and the number of pores formed were directly related to the initial level of pore former (guar gum) in spm. the manufacturing procedure was found to be reproducible and formulations were found to be stable during 3 months of accelerated stability studies.